Alien and invasive Poaceae weed species in Madagascar: listing and recommendations - Randrianarimanana, Noro Fenitra Harimbao; Randriamampianina, Jean Augustin; Rakotomalala, Nantenaina Herizo; Rakotoarinivo, Mijoro; Rafidison, Verohanitra Miarivelomalala; Vorontsova, Maria Sergeevna (African Biodiversity & Conservation, 2026)
Recent research has improved the understanding of the Poaceae family in Madagascar, particularly in terms of taxonomy. These studies have facilitated better identification and classification of species. However, little attention has been given to alien and invasive Poaceae weed species, despite their important role in ecological dynamics. This gap highlights the need to investigate the invasive potential of this plant family, which can significantly impact Madagascar’s ecosystems. In this study, we aim to advance the understanding of Poaceae invasions by reviewing existing data and highlighting key insights to support Madagascar’s invasive species management. We developed a comprehensive checklist of 154 Poaceae weeds and/or alien species based on literature reviews and online databases to ensure accuracy and comprehensiveness. Our goal was to categorise these species into groups with three distinct management recommendations: prohibited species, species that need to be monitored and those considered harmless. Each of these categories was defined based on its estimated ecological impact and invasiveness potential. Among the 154 species assessed, we confirmed the presence of 56 species introduced to Madagascar and identified one species that we suggest should be prohibited in Madagascar. Based on our assessment, we propose a precautionary approach for species that are not yet invasive but pose a threat. Additionally, we highlight species that should be subject to risk analysis to assess their invasive potential. By developing these recommendations, we hope to assist in the creation of effective strategies for managing Poaceae invasions in Madagascar and to support broader conservation efforts.